Media activism and alternative media: congruencies and particularities in the context of information and communication technologies - Ramalho, Raul (2022)
The paper points out intersections and theoretical-empirical differences between alternative media and media activism relating conceptions about the aforementioned forms of activism through the media with empirical examples taken from the discursive performance of Mídia Ninja and Jornalistas Livres, in Facebook posts, during the 2018 elections in Brazil. The analyzes suggest that alternative media concepts and practices are intertwined with media activism. This is detached from the first designation due to the conformations that the information and communication technologies confer to the current activism, but not determining it, since the centrality of the human being in socio-technical action is maintained.